The Contemporary House of Lords : Westminster Bicameralism Revived - Russell, Meg. (Oxford : Oxford University Press, 2013)
As the second chamber of the Westminster parliament, the House of Lords has a central position in British politics. But it is far less well-studied and well understood than the House of Commons. This is in part because of constant expectations that it is about to be reformed - but most Lords reform plans fail, as the Coalition government's dramatically did in 2012. Meanwhile, following a landmark change in 1999 which removed most of its hereditary members, the Lords' role in the policy process has grown. Understanding the chamber is therefore now essential to understanding politics and parliament in Britain. This book provides the first detailed portrait of the post-1999 Lords, explaining who sits in the chamber, how it operates, and crucially what policy impact it has. Its membership is shown to be more diverse and modern than many would assume, and its influence on policy to be substantial. As a 'no overall control' chamber, in which no party has a majority, it has inflicted numerous defeats on the Blair, Brown and Cameron governments, and become an important site of negotiation. It has provided a power base for the Liberal Democrats, and includes a group of almost 200 independents who now play a pivotal role. --
Introduction -- Context -- A brief history of the House of Lords -- Bicameralism in theory and comparative perspective -- The post-1999 House of Lords -- A breif introduction to the contemporary House of Lords -- Political actors in the Lords -- The Lords as a barrier to government : legislative defeats -- Negotiated outcomes and the wider legislative impact of the Lords -- Non-legislative policy work -- Is the House of Lords 'legitimate'? : attitudes towards the chamber -- The future -- The politics of Lords reform -- Conclusions : the House of Lords, British politics and legislative bicameralism -- Bbiliography -- Index of Names -- Index.
Includes bibliographical references (pages: [301]-315) and indexes.
Keywords: Great Britain. -- Parliament. -- House of Lords -- Reform; Legislative bodies -- Great Britain -- Reform; Great Britain -- Politics and government -- 1997-2007; Great Britain -- Politics and government -- 2007-